Factors Influencing Parental Compliance in Bringing Their Children to Undergo Chemotherapy at Dr. Cipto Mangunkusumo Hospital - Lina Dewi Anggraeni; Ernita Kandi Utami Siebel (UIMA Press, 2022)
Background: Cancer is a disease that can be treated with several therapies, including chemotherapy. Chemotherapy is a type of anti-cancer drug treatment that works by killing cancer cells. Currently, this medical treatment has been covered by the national health insurance which is managed by the government that aimed at providing assurance of social protection and welfare. Adherence to chemotherapy is one of the treatments that can improve the quality of life of children with cancer. Objectives: The aim of this study is to identify the factors influencing parental adherence to bring their child undergoing chemotherapy. Methods: The research method was quantitative, employing a descriptive correlation approach and a cross-sectional design. The data was collected using a questionnaire. The sample was 96 parents of children who underwent chemotherapy, which taken by accidental sampling. Chi-square, Kendall's Tau B, and Kendall's Tau C were used in the analysis. Results: There was a significant relationship between education level (p value = 0.006), knowledge (p value = 0.003), and no relationship with work (p value = 0.291), economic status (p value = 0.269), distance (p value = 0.389), side effect (p value = 0.624), and support system (p value = 0.309) with the adherence of parents in bringing their children to chemotherapy. Conclusion: Health professionals can monitor and encourage parents to always bring their children to chemotherapy.